Maternal tributyrin supplementation in late pregnancy and lactation improves offspring immunity, gut microbiota, and diarrhea rate in a sow model - Lin, Yan; Li, Dan; Ma, Zhao; Che, Lianqiang; Feng, Bin; Fang, Zhengfeng; Xu, Shengyu; Zhuo, Yong; Li, Jian; Hua, Lun; Wu, De; Zhang, Junjie; et al. (Frontiers in Microbiology, 2023)
The purpose of this study was to investigate the effects of tributyrin on the reproductive performance of lactating sows and metabolic parameters and gut microbiota in sows and their offspring. Thirty sows (Landrace × Yorkshire) were randomly divided into two groups: the control group (CON) and the tributyrin group (TB), which received basal diet supplemented with 0.05% tributyrin. The experimental period lasted for 35 days from late pregnancy to lactation. The results showed that TB supplementation significantly shortened the total parturition time and reduced the diarrhea rate in suckling piglets. On day 20 of lactation, the milk fat and protein levels increased by 9% and 4%, respectively. TB supplementation significantly improved the digestibility of dry material, gross energy, and crude fat in the sow diet, but had no significant effect on crude protein digestibility. Furthermore, TB supplementation increased the levels of IL-10, IL-6, and IgA in the blood of weaned piglets, but had no effect on maternal immunity. Analysis of the fecal microbial composition revealed that the addition of TB during late gestation and lactation increased the microbiota diversity in sows and piglets. At the phylum level, sows in the TB group had a slight increase in the relative abundance of Bacteroidota and Spirochaetota and a decrease in Firmicutes. At the order level, the relative abundance of Lactobacillales was significantly increased in piglets and sows, and the TB group showed increased relative abundance of Enterobacter and decreased relative abundance of Oscillospirales in piglets. At family level, the relative abundance of Lactobacillaceae, Oscillospiraceae, and Christensenellaceae significantly increased in sows, and the relative abundance of Enterobacteriaceae and Lactobacillaceae significantly increased in piglets. At genus level, the relative abundance of Lactobacillus significantly increased in sows and piglets, but the relative abundance of Subdoligranulum and Eubacterium_fissicatena_group decreased in piglets in the TB group. In conclusion, supplementation with 0.05% tributyrin in late pregnancy and lactation shortened the parturition time and improved the nutrient digestibility of sows, thereby reducing the rate of occurrence of in suckling piglets by improving the immunity and composition of the intestinal microflora in sows and their offsprings.